2017
DOI: 10.1021/jacs.7b07768
|View full text |Cite
|
Sign up to set email alerts
|

“Sweet” Architecture-Dependent Uptake of Glycocalyx-Mimicking Nanoparticles Based on Biodegradable Aliphatic Polyesters by Macrophages

Abstract: Glyconanoparticles made by self-assembled glycopolymers currently are practical and efficient mimics of the glycocalyx on cell surfaces. Considering the complexity of the glycocalyx, glyconanoparticles with different sugars on their coronas, i.e., mixed-shell glycomicelles, could be more valuable compared to homoshell micelles. In this paper, we explore the architectural effect of the glyconanoparticle corona on glyconanoparticle macrophage endocytosis and lectin-binding ability. A series of glyconanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 69 publications
3
73
0
2
Order By: Relevance
“…More importantly, dextran‐based adjuvants could not only activate tumor‐specific CTL responses, but also inhibit myeloid‐derived suppressor cells (MDSCs) in tumor immune microenvironment . Many works indicate that binding between C‐type lectin receptors (CLRs) and carbohydrate ligands is important not only for the induction of T‐cell responses, but also for the inhibition of immunosuppressive microenvironment . Therefore, lymphoseek‐inspired vaccine should have advantages of promoting vaccine internalization, potentiating CD8 + T‐cell responses and reducing the immunosuppressive activity, and become a promising candidate for next‐generation cancer vaccine.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, dextran‐based adjuvants could not only activate tumor‐specific CTL responses, but also inhibit myeloid‐derived suppressor cells (MDSCs) in tumor immune microenvironment . Many works indicate that binding between C‐type lectin receptors (CLRs) and carbohydrate ligands is important not only for the induction of T‐cell responses, but also for the inhibition of immunosuppressive microenvironment . Therefore, lymphoseek‐inspired vaccine should have advantages of promoting vaccine internalization, potentiating CD8 + T‐cell responses and reducing the immunosuppressive activity, and become a promising candidate for next‐generation cancer vaccine.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated the modulation ability of the glycocalyx‐mimicking NPs (GNPs) on M2‐like TAMs by reduction of suppressive functions . To develop the nanostructures with better stability and functionality, mimicking glycocalyx, an important cell surface structure of polymeric sugar layer, has become a promising strategy for the rational design of targeted nanocarriers, since the architecture of glycocalyx has been found to greatly influence the sugar‐receptor interaction, as well as uptake by macrophages or cancer cells . In this regard, Zhang et al incorporated αPD‐L1 mAb into the self‐assembled mannose‐functionalized GNPs targeting TME to restore immune functions in the TME by promoting the reversion of TAMs, and thus enhance the αPD‐L1 therapeutic effect by decreasing tumor resistance (Figure ) .…”
Section: Mannose‐based Nanomaterials In Biomedical Applicationsmentioning
confidence: 99%
“…It highlighted a strategy for engineering a biosourced polysaccharide with surface moieties that exhibited strong multivalent interactions with lectins, and targeted interaction with prostate cancer cells. Wu et al (2017) explored the architectural effect of the glyconanoparticle corona on glyconanoparticle macrophage endocytosis and lectin-binding ability. Nanoparticles with a mixed shell showed a higher efficiency in cellular uptake and lectin-binding than those with a single sugar component.…”
Section: Magnetic Glyconanoparticlesmentioning
confidence: 99%